2005
DOI: 10.1007/s10517-005-0437-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurosis-Associated Changes in the Granulocytic Hemopoietic Stem in Mice with Different Learning Capacity

Abstract: We studied the local mechanisms of neurosis-associated changes in the granulocytic hemopoietic stem in CBA/CaLac mice with different learning capacity. It was found that in good learners hyperplasia of the bone marrow granulocytopoiesis during neurosis was related to enhanced proliferative activity and accelerated maturation of granulocyte-macrophage precursors resulting from increased formation of granulocytic and erythrogranulocytic hemopoietic islets. In poor learners primary suppression of the bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In many cases it was caused by neglect of individual patient's characteristics. We previously developed a method for studies of hemopoiesis in experimental animals with consideration for individual features of their higher nervous activity [9]. Changes in the blood system under extreme conditions (immobilization stress, hypoxic trauma, ex perimental neurosis) depended on the initial behavioral activity and conditioned refl ex habits [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases it was caused by neglect of individual patient's characteristics. We previously developed a method for studies of hemopoiesis in experimental animals with consideration for individual features of their higher nervous activity [9]. Changes in the blood system under extreme conditions (immobilization stress, hypoxic trauma, ex perimental neurosis) depended on the initial behavioral activity and conditioned refl ex habits [3].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of IMON on the blood system of animals with initially high (group 1) and low (group 2) behavioral activity were studied by the method for hemopoiesis studies with consideration for individual higher nervous activity [9].…”
Section: Methodsmentioning
confidence: 99%
“…The severity of changes in conditioned activity after conflict situation is mainly determined by emotional reactivity of animals. High emotional reactivity of good learners explains the fact that subjective perception of paradoxical sleep deprivation and conflict situation in these animals led to significant changes in the blood system [9,11]. When discussing the differences in behavioral activity of CBA/CaLac mice, we should emphasize that CBA, CBA/Lac, and C57Bl/6 mice are divided into groups of behaviorally aggressive and submissive specimens under conditions of sensory contact [1,7].…”
Section: Resultsmentioning
confidence: 99%
“…Confl ict situation and immobilization stress were followed by similar stimulation of the bone marrow erythropoiesis and granulomonocytopoiesis. By contrast, sleep disorders were shown to cause suppression of the erythron and abortive hyperplasia of the granulocytic hemopoietic stem [15,24,[30][31][32]42,44,47,57]. Experiments with neurophar maco logi cal agents of the central action (sympatholytic, neuroleptic, and antiserotonin products) showed that plastic reconstruction of the blood system during neuroses is regulated by the adrenergic, dopaminergic, and serotoninergic systems [10,12,13,24,29,42,48,49,52,54,56,59,60].…”
mentioning
confidence: 99%